New ‘global dark age’ : has everything changed? - Garfinkle, Adam (2020)
As the fourth global psycho-seismic shock, the COVID-19 pandemic has destabilising impacts. It is futile to predict the road ahead. Will it lead to a new “Global Dark Age”, or unprecedented progress?